Lenalidomide-induced arthritis: A case report and review of literature and pharmacovigilance databases. (March 2022) - Icard, Charlotte; Mocquot, Pauline; Nogaro, Jean-Claude; Despas, Fabien; Gauthier, Martin
Introduction: Lenalidomide is an immunomodulatory agent with multiple mechanisms of action, and treatment with lenalidomide is associated with adverse events such as thrombosis and abdominal pain; nonetheless, other rarer adverse events do exist, with few knowledge from physicians and pharmacists. For such adverse events, pharmacovigilance databases are of great interest. Case report: A 71-year-old patient with no rheumatologic history, in complete remission of a mantle-cell lymphoma following rituximab, doxorubicin, vincristine, cyclophosphamide, and prednisone induction, received a maintenance treatment with rituximab and lenalidomide. After each course of lenalidomide and with no other new medication, the patient presented with fever and high inflammatory markers level, and a scapular-belt arthritis. Management and outcome: The patient was managed with non-steroidal anti-inflammatory drugs and colchicine, with symptomatology and inflammation improvement. After discontinuation of lenalidomide, he had no arthritis relapse; it was then concluded that the patient had a lenalidomide-induced arthritis. We interrogated the national and international (VigiBase®) pharmacovigilance databases and found that arthritis in the context of lenalidomide exposure is a rare finding, with only three reported cases in France; 0.13% of adverse events reported with lenalidomide in the international database VigiBase® were arthritis. Discussion: Our case then reports an uncommon finding, of which both pharmacists and physicians should be aware due to the wide and increasing use of lenalidomide.